Producción científica sobre brecha digital en Latinoamérica y Asia - Laura Paima, Emily Cecilia (2024)
The objective of the research was to analyze scientific production on the digital divide from 2006 to 2023 in high-impact (Scopus) and regional (Redalyc) databases. The aim was to identify similarities, common results, and both positive and negative aspects of the studies. The narrative literature review study analyzed 30 scientific articles. For the processing of the information, analysis matrices were used as instruments, taking into account individual, social, and cultural factors. The findings reveal that the digital divide continues to impact societies, especially those in vulnerable situations, such as low-income individuals, the elderly, people with disabilities, and residents of rural areas. The research has provided valuable information on this phenomenon, which is used to create laws and programs aimed at reducing the digital divide. In conclusion, the importance of considering both the ability to use devices and technology, as well as access to them, is emphasized. The need for specialized approaches that take into account a range of variables, such as age, educational level, and affordability, to address discrepancies in technology adoption in rural areas, is also highlighted.